Cortical phase changes measured using 7‐T MRI in subjects with subjective cognitive impairment, and their association with cognitive function. (19th December 2014) - van Rooden, Sanneke; Buijs, Mathijs; van Vliet, Marjolein E.; Versluis, Maarten J.; Webb, Andrew G.; Oleksik, Ania M.; van de Wiel, Lotte; Middelkoop, Huub A. M.; Blauw, Gerard Jan; Weverling‐Rynsburger, Annelies W. E.; Goos, Jeroen D. C.; van der Flier, Wiesje M.; et al.
Abstract : Studies have suggested that, in subjects with subjective cognitive impairment (SCI), Alzheimer's disease (AD)‐like changes may occur in the brain. Recently, an in vivo study has indicated the potential of ultra‐high‐field MRI to visualize amyloid‐beta (Aβ)‐associated changes in the cortex in patients with AD, manifested by a phase shift on T 2 *‐weighted MRI scans. The main aim of this study was to investigate whether cortical phase shifts on T 2 *‐weighted images at 7 T in subjects with SCI can be detected, possibly implicating the deposition of Aβ plaques and associated iron. Cognitive tests and T 2 *‐weighted scans using a 7‐T MRI system were performed in 28 patients with AD, 18 subjects with SCI and 27 healthy controls (HCs). Cortical phase shifts were measured. Univariate general linear modeling and linear regression analysis were used to assess the association between diagnosis and cortical phase shift, and between cortical phase shift and the different neuropsychological tests, adjusted for age and gender. The phase shift (mean, 1.19; range, 1.00–1.35) of the entire cortex in AD was higher than in both SCI (mean, 0.85; range, 0.73–0.99; p < 0.001) and HC (mean, 0.94; range, 0.79–1.10; p < 0.001). No AD‐like changes, e.g. increased cortical phase shifts, were found in subjects with SCI compared with HCs. In SCI, a significant association was found between memory function (Wechsler Memory Scale, WMS) and cortical phase shift ( β = –0.544, p = 0.007). The major finding of this study is that, in subjects with SCI, an increased cortical phase shift measured at high field is associated with a poorer memory performance, although, as a group, subjects with SCI do not show an increased phase shift compared with HCs. This increased cortical phase shift related to memory performance may contribute to the understanding of SCI as it is still unclear whether SCI is a sign of pre‐clinical AD. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In subjects with subjective cognitive impairment (SCI), Alzheimer's disease‐like changes may occur in the brain. We investigated whether cortical phase shifts at 7 T in SCI can be detected, implicating the deposition of amyloid‐beta (Aβ) plaques and associated iron, and which cognitive domains are associated with cortical phase shifts in SCI. In SCI, an increased cortical phase shift at high field is associated with a poorer memory performance, although no increased phase shift could be determined in subjects with SCI compared with controls.